Stomata Characteristics, stomatal density and stomatic index in redwood (Sequoia sempervirens) and its variation in different plantations in Chile - Toral, Manuel; Manríquez, Adelina; Navarro-Cerrillo, Rafael; Tersi, Denise; Naulin, Paulette (Bosque (Valdivia), 2017)
Several authors suggest that the stomata of Sequoia sempervirens (redwood) may present morphological changes when this species grows in areas without the presence of crypto-precipitation. This work studied the characteristics of the stomata, density and stomata index in leaves of redwood in terms of precipitation level, soil, slope exposition and location in the forest stand. The anatomical study was made by diaphanization and staining techniques of the leaf samples. The main results of this work indicate that the sequoia stomata, in the populations studied, are smaller than those from natural populations, with an average length between 31.4 and 37.7 µm and an average width between 12.6 and 14.9 µm; mainly found in the abaxial epidermis. Their density varied between 81.3 and 111.4 stomata mm–2, with an average stomatic index between 15.5 and 21.1 depending on the locality studied. These values are in ranks lower than those found for the species by other authors; indicating a certain degree of acclimation for the species in Chile. While there was significant variation among localities in Chile, changes in the stomatal complex were not so evident in response to the site environmental characteristics. However, in areas with more restraining climatic conditions (lower atmospheric humidity and precipitation), combined with edaphic conditions (soil with greater apparent density or less depth), stomata showed smaller and less dense, revealing a significant degree of phenotypic plasticity of the species for the character studied, which allows adaptation processes to contrasting environmental situations.